Asesmen Perkembangan Sosial Anak Usia 5 Tahun melalui Observasi Naturalistik: Assessment of Social Development of 5 Year Old Children Through Naturalistic Observation - Mardiyah; Sakinah; Lia Khaerunnisa (Universitas Ngudi Waluyo, 2025)
This study aims to describe the social development of 5-year-old children through naturalistic observation methods in the context of early childhood education. A descriptive qualitative approach was employed to gain an in-depth understanding of children's social behavior in three different settings: home, school, and a recreational environment. The research subjects consisted of three 5-year-old children who were observed directly without intervention. Data were collected through anecdotal records, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that each child demonstrated varying levels of social readiness when interacting with their surroundings. Emotional support from adults and previous experiences influenced their initiative to build social relationships. These findings suggest that naturalistic observation is an effective assessment method for understanding children's social interactions authentically and serves as a valuable basis for planning appropriate social stimulation. This study contributes to the development of context-based formative assessments to comprehensively evaluate early childhood social development. ABSTRAK Penelitian ini bertujuan untuk menggambarkan perkembangan sosial anak usia 5 tahun melalui metode observasi naturalistik dalam konteks pendidikan anak usia dini. Pendekatan kualitatif deskriptif digunakan untuk memperoleh pemahaman yang mendalam mengenai perilaku sosial anak di tiga lingkungan berbeda, yaitu rumah, sekolah, dan tempat wisata. Subjek penelitian terdiri dari tiga anak berusia 5 tahun yang diamati secara langsung tanpa intervensi. Data dikumpulkan melalui catatan anekdot, wawancara, dan dokumentasi, lalu dianalisis dengan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa setiap anak memiliki tingkat kesiapan sosial yang berbeda dalam berinteraksi dengan lingkungan sekitarnya. Dukungan emosional dari orang dewasa dan pengalaman sebelumnya memengaruhi inisiatif anak dalam menjalin hubungan sosial. Temuan ini menunjukkan bahwa observasi naturalistik merupakan metode asesmen yang efektif untuk memahami proses interaksi sosial anak secara autentik, serta menjadi dasar penting bagi perencanaan stimulasi sosial yang sesuai. Penelitian ini berkontribusi dalam pengembangan asesmen formatif berbasis konteks nyata untuk menilai perkembangan sosial anak usia dini secara komprehensif.